Structural Properties, Conductivity, Dielectric Studiesand Modulus Formulation of Ni Modified ZnO Nanoparticles (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
In the present manuscript, we have reported the structural, ac conductivity, dielectric studies and modulus formulation of Zn$_{1-x}$Ni$_x$O $(x=0.00,0.10,0.20,0.30)$ nanoparticles synthesized by sol-gel technique. The Rietveld refinement of X-ray powder diffraction data reveals that the samples possess hexagonal structure (space group - P63mc) of ZnO. The low intensity diffraction peaks corresponding to NiO comes into existence, it is suggested that phase segregation has occurred in the Ni doped ZnO nanoparticles. Average crystallite size has been estimated from XRD patterns, which is found to increase with increase in Ni content. AC conductivity and dielectric properties of Ni doped ZnO nanoparticles have been studied as a function of frequency (100 Hz to 10 MHz) of the applied ac signal in the temperature range of 323K to 463 K. The results showed that ac conductivity increases while other parameters such as the real dielectric constant $ε'$ and dielectric loss $\tanδ$ decreases with frequency of applied field. The values of parameters $ε'$, $\tanδ$ and ac conductivity are found to increase with increase temperature. In all the samples small polaron conduction mechanism is predominant. The variation of $ε'$, $\tanδ$ and ac conductivity is observed to increase with increase in Ni dopant concentration in ZnO. The results of electrical modulus to study the relaxation dynamics of charge carriers indicate the presence of non-Debye type of relaxation in present samples.
Keywords: Sol-gel technique; Rietveld refinement; AC conductivity; Dielectric studies